The Sphingolipid Inhibitors Ceranib-2 and SKI-II Reduce Measles Virus Replication in Primary Human Lymphocytes: Effects on mTORC1 Downstream Signaling - Chithelen, Janice; Franke, Hannah; Länder, Nora; Grafen, Anika; Schneider-Schaulies, Jürgen (Frontiers in Physiology, 2022)
The bioactive sphingolipids ceramide and sphingosine-1-phosphate (S1P) are involved in the regulation of cell homeostasis and activity ranging from apoptosis to proliferation. We recently described that the two compounds ceranib-2 (inhibiting acid ceramidase) and SKI-II (inhibiting the sphingosine kinases 1 and -2 (SphK1/2)) reduce mTORC1 activity and measles virus (MV) replication in human primary peripheral blood lymphocytes (PBL) by about one log step. We now further investigated whether mTORC1 downstream signaling and viral protein expression may be affected by ceranib-2 and/or SKI-II. Western blot analyses showed that in uninfected cells the phosphorylation of the eukaryotic initiation factor 4E (eIF4E) was reduced by both inhibitors. Interestingly, MV infection led to an increase of rpS6 protein levels and phosphorylation of eIF4E. Treatment with both inhibitors reduced the rpS6 protein expression, and in addition, SKI-II reduced rpS6 phosphorylation. The phosphorylation of eIF4E was slightly reduced by both inhibitors. In addition, SKI-II led to reduced levels of IKK in MV-infected cells. Both inhibitors reduced the expression of viral proteins and the titers of newly synthesized MV by approximately one log step. As expected, SKI-II and rapamycin reduced also the virally-encoded GFP expression, however, ceranib-2 astonishingly led to increased levels of GFP fluorescence. Our findings suggest that the inhibitors ceranib-2 and SKI-II act via differential mechanisms on MV replication. The observed effects on mTORC1 downstream signaling, predominantly the reduction of rpS6 levels by both inhibitors, may affect the translational capacity of the cells and contribute to the antiviral effect in human primary PBL.